CURRICULUM INNOVATION IN LANGUAGE INSTRUCTION: ADAPTING TO CHANGING LEARNER NEEDS - Rozak, Dinda Luthfiana; Ayaz, Maria (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
This study aims to explore curriculum innovation in language teaching, focusing on the integration of language development and academic content, and to assess its impact on student engagement and learning outcomes. The research employs a literature review method, analyzing various academic sources that discuss curriculum innovation in language teaching. These sources include peer-reviewed articles that focus on issues related to curriculum design, language integration, and cultural considerations. The findings of the study indicate that an integrated approach that combines language development with academic content can enhance student engagement and overall learning outcomes. The integration of culture into the curriculum is also found to be crucial for building linguistic and cultural awareness among students. However, implementing curriculum changes requires careful planning and ongoing support for educators and students. The study emphasizes the need for a balance between innovation and stability in language teaching to ensure that the changes made genuinely improve the student learning experience and prepare them for the challenges of an increasingly complex world.